MENINGKATKAN KEMAMPUAN BERBICARA SISWA DENGAN PENDEKATAN KOMUNIKATIF KELAS XI IPA SMA NEGERI 1 SUKOSARI BONDOWOSO: SMA NEGERI 1 SUKOSARI BONDOWOSO - YUDI KURNIAWAN (Mitra Pendidikan, 2021)
This study aims to improve the Efforts to Improve Students' Speaking Ability With a Communicative Approach for Class XI Natural ScienceSenior High School I Sukosari for the 2017-2018 academic year. Classroom action research is an option and is carried out to solve learning problems in two cycles. The stages of the cycle are passed through two stages with two meetings in each cycle. The data obtained through the results of learning and observation. The analysis technique was carried out in a quantitative descriptive manner. The initial condition is that only 10 students or 47% have completed, in the first cycle there are 14 students or 67% whose scores have been completed, after the activities in the second cycle have increased, there are 20 students or 95% who have completed so that in the second cycle there is only 1 student. or 5% who have not reached the minimum completeness criteria value.